1986
DOI: 10.1289/ehp.8669275
|View full text |Cite
|
Sign up to set email alerts
|

Type of disinfectant in drinking water and patterns of mortality in Massachusetts.

Abstract: Chlorination has been the major strategy for disinfection of drinking water in the United States. Concern about the potential health effects of the reaction by-products of chlorine has prompted use of alternative strategies. One such method is chloramination, a treatment process that does not appear to have carcinogenic by-products, but may have less potent biocidal activity than chlorination.We examined the patterns of mortality of residents in Massachusetts who died between 1969 and 1983 and lived in communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Several case-control studies supported an association between consumption of water from public sources and increased risk of bladder cancer. Some studies found that tap water with chlorine-and hence containing chlorination byproducts-may increase the risk of bladder cancer (Wilkins & Comstock, 1981;Gottlieb & Carr, 1982;Zierlier et al, 1986Zierlier et al, , 1988Cantor et al, 1987Cantor et al, , 1998McGeehin et al, 1993;Koivusalo et al, 1994;King & Marrett, 1996;Kiemeney & Schoenberg, 1996;Freedman et al, 1997). Arsenic in drinking water has also been associated with increased risk of bladder cancer (Chen et al, 1986(Chen et al, , 1992Wu et al, 1989;Bates et al, 1995;Hopenhayn-Rich et al, 1996;Chiou et al 2001), but it is unclear whether the levels of arsenic in drinking water from developed countries have any meaningful effect.…”
Section: European Journal Of Clinical Nutritionmentioning
confidence: 99%
“…Several case-control studies supported an association between consumption of water from public sources and increased risk of bladder cancer. Some studies found that tap water with chlorine-and hence containing chlorination byproducts-may increase the risk of bladder cancer (Wilkins & Comstock, 1981;Gottlieb & Carr, 1982;Zierlier et al, 1986Zierlier et al, , 1988Cantor et al, 1987Cantor et al, , 1998McGeehin et al, 1993;Koivusalo et al, 1994;King & Marrett, 1996;Kiemeney & Schoenberg, 1996;Freedman et al, 1997). Arsenic in drinking water has also been associated with increased risk of bladder cancer (Chen et al, 1986(Chen et al, , 1992Wu et al, 1989;Bates et al, 1995;Hopenhayn-Rich et al, 1996;Chiou et al 2001), but it is unclear whether the levels of arsenic in drinking water from developed countries have any meaningful effect.…”
Section: European Journal Of Clinical Nutritionmentioning
confidence: 99%
“…Miettinen and Wang (1981: 147) liken the analysis of the mortality odds ratio to a type of case-control study, noting "the totality of deaths from the cause of interest, combining the exposed and nonexposed domains, can be thought of as a case series; and all the 'other' deaths can be thought of as a reference series for the cases-if exposure is not a risk indicator for death from those 'other' causes." Adopting a multivariate approach to analysis using logistic regression, researchers can then compare the odds ratios for a particular cause of death or disease cluster with reference to a particular risk factor (or "exposure") of interest, while also controlling for other confounding variables (see, for example, Burke and Sawchuk 2003;Lee et al 2003;Wray et al 2008;Zaridze et al 2009;Zierler et al 1986). When assessing mortality odds ratios, the entire study is conditioned on dying (i.e., all those individuals included in the analysis have died).…”
Section: Methodsmentioning
confidence: 99%
“…The study by Freedman was considered in an alternative analysis. Death certificate based case-control studies, [18][19][20] although have been frequently quoted, were not included in this meta-analysis because exposure information was either ecological or based on interviews of proxies…”
Section: Datamentioning
confidence: 99%